Risk and Inequality in a Social Decision Making Experiment - Ingrid M.T. Rohde; Kirsten I.M. Rohde (Tinbergen Institute, 2012)
As societies are increasingly concerned with social risks, it is important to evaluate risks not only from an individual perspective, but also from a societal one. Many increases in social risk involve a simultaneous increase in risk and inequality. This paper presents an experiment which disentangles concerns for risk and inequality in a social risk context. Subjects choose between different types of allocations of risks over 10 other participants. The allocations differ only in terms of dispersion. We disentangle four types of dispersion: ex ante inequality, ex post inequality, individual risk, and collective risk. The results show that people are averse towards ex ante inequality and individual risk, whereas they are ex post inequality and collective risk seeking.
urn:NBN:nl:ui:15-1765/32664
Keywords: D03; D63; 330; inequality; risk; experiment; Risikopräferenz; Entscheidung bei Risiko; Soziale Beziehungen; Test